A comparative of study the design spectra defined by various seismic codes - Elmi, Khadar Abdilahi (İstanbul Kültür Üniversitesi / Lisansüstü Eğitim Enstitüsü / İnşaat Mühendisliği Ana Bilim Dalı / Yapı Mühendisliği Bilim Dalı, 2020)
Depremler kısa sürede büyük kuvvetler oluştururlar. Büyüklüğü küçük olan depremlerde tüm yapıların çökmeden ayakta kalabilmesi oldukça önemlidir. Bu çalışmanın temel amacı, Türkiye Bina Deprem Yönetmeliği (TBDY-2018), Hindistan Yönetmeliği (IS 1893-1, 2016), Eurocode (EN1998-1: 2004) ve ABD Yönetmeliklerinin (ASCE7-), davranış spektrumu modellerini karşılaştırmaktır. Deprem analizinde en yaygın yöntem doğrusal analizdir ve genellikle yeni yapıların tasarımında kullanılır. Çalışmada karşılaştırma yapmak amacıyla altı katlı moment çerçevesi modeli ele alınmış ve tasarım ve analizler için gerekli model SAP2000-v20 yazılımı kullanılarak oluşturulmuştur. Analizler, tepki spektrumları ve eşdeğer yatay kuvvet yöntemi kullanılarak yapılmıştır. Periyotlar, yatay yer değiştirme ve modal kütle katılım

Earthquakes create numerous forces in a short period. It is very important for all structures to withstand small earthquakes without collapse. The main purpose of this study, Turkey Building Earthquake Code (TBDY-2018), India Code (IS 1893-1, 2016), Eurocode (EN1998-1: 2004), and USA Code of (ASCE7-) to compare the behavior spectrum models. The most common method in earthquake analysis is the linear analysis and is generally used in the design of new structures. A six-story moment frame model was considered in the study for comparison and the required model for design and analysis was created using SAP2000-v20 software. Analyzes were performed using response spectra and the equivalent horizontal force method. Results such as periods, horizontal displacement, and modal mass participation ratio are interpreted by comparing them with graphs and tables.
Keywords: İnşaat Mühendisliği; Civil Engineering